2020
DOI: 10.1016/j.cdtm.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy strategies for advanced gastric cancer: Current innovations and future challenges

Abstract: Gastric cancer, which has a high incidence and poor prognosis, remains a therapeutic challenge. Recently, neoadjuvant therapy has attracted increasing attention due to high recurrence rate and low survival rate after resection in most patients with advanced stage. Clinical trials show that neoadjuvant approaches confer a significant survival advantage for resectable locally advanced gastric cancer. The specific advantages of chemoradiotherapy compared with chemotherapy have not been clarified; optimal regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Several classic clinical trials have indicated GAC patients derive a survival benefit from postoperative adjuvant chemotherapy, which has led to it being widely recommended as standard therapy, especially for stage II and III patients [31,32]. However, there have been large variations in chemotherapy response and clinical outcomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several classic clinical trials have indicated GAC patients derive a survival benefit from postoperative adjuvant chemotherapy, which has led to it being widely recommended as standard therapy, especially for stage II and III patients [31,32]. However, there have been large variations in chemotherapy response and clinical outcomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…CDDP has been used for years as a first-line treatment for several cancer types, either alone or in combination with other therapeutic options, such as radiation (to serve as a radiosensitizer) or other chemotherapeutics [ 18 ]. It is usually administered as either a neoadjuvant (for tumor shrinkage) or adjuvant (to lessen the risk of recurrence) therapy [ 19 , 20 , 21 ]. It may also be used in a palliative chemotherapy scenario, due to its cytotoxic activity, in an attempt to maintain patient quality of life [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also a common gastrointestinal malignant tumor and ranks the fourth cause of death of malignant tumors [ 1 ]. Despite the recent advances in chemotherapy, radiotherapy and surgery for the treatment of GC, the survival rate of GC patients was still unsatisfactory [ 2 , 3 ]. It was reported that the lack of appropriate molecular biomarkers was one of the main reasons for the low overall survival rate of GC patients, as a result, without effectively early diagnosis, most GC patients missed the best opportunity for surgical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%